2017
DOI: 10.1016/j.jhin.2017.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Multi-site and nasal swabbing for carriage of Staphylococcus aureus : what does a single nose swab predict?

Abstract: SummaryBackgroundCarriage of Staphylococcus aureus is a risk for infections. Targeted decolonization reduces postoperative infections but depends on accurate screening.AimTo compare detection of S. aureus carriage in healthy individuals between anatomical sites and nurse- versus self-swabbing; also to determine whether a single nasal swab predicted carriage over four weeks.MethodsHealthy individuals were recruited via general practices. After consent, nurses performed multi-site swabbing (nose, throat, and axi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 28 publications
2
18
0
1
Order By: Relevance
“…This highlights the possible utility of testing for skin carriage or nasal carriage alone to detect a possible carrier status. Prior studies have con rmed this and shown that nasal swabbing alone is adequate (8,9). This is in keeping with the results from our study.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…This highlights the possible utility of testing for skin carriage or nasal carriage alone to detect a possible carrier status. Prior studies have con rmed this and shown that nasal swabbing alone is adequate (8,9). This is in keeping with the results from our study.…”
Section: Resultssupporting
confidence: 93%
“…This is in keeping with the results from our study. A few studies have higher detection rates using throat swabbing (8,9). We did not adopt this due to inconvenience to the patient.…”
Section: Resultsmentioning
confidence: 99%
“…19,21,24 They used nasal/nasopharyngeal swabs, but the literature does not mention major differences in detection of S aureus between nose or throat. 34 Another explanation is the use of PCR for detection of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…This study has certain limitations. Cultures were only obtained by nasal swab, as the association with surgical site infections is strongest with nares cultures; however, while the addition of other sites such as the throat or the surgical site might increase in culture yield, the increase is unlikely to be large (4,(32)(33)(34). Moreover, a difference in carriage would likely affect all three tested groups equally.…”
Section: Discussionmentioning
confidence: 99%